2002
DOI: 10.1177/152660280200900304
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Inflammatory Abdominal Aortic Aneurysms

Abstract: IAAA may be successfully excluded by the endovascular technique, and EVAR is particularly useful where open repair has failed. The impact of endograft placement on perianeurysmal fibrosis is less clear. In this study, there was no suggestion that the degree of PAF worsens following endovascular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…In contrast, Hinchliffe et al [3] reported a regression of periaortic fibrosis in three of six patients (50%) and an unchanged situation in the remaining three. We observed even better results, with a regression of the inflammatory tissue and the periaortic fibrosis in all five patients and a complete disappearance in three of them These facts enforce endovascular aneurysm repair as an attractive alternative with better results in the regression of periaortic fibrosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, Hinchliffe et al [3] reported a regression of periaortic fibrosis in three of six patients (50%) and an unchanged situation in the remaining three. We observed even better results, with a regression of the inflammatory tissue and the periaortic fibrosis in all five patients and a complete disappearance in three of them These facts enforce endovascular aneurysm repair as an attractive alternative with better results in the regression of periaortic fibrosis.…”
Section: Discussionmentioning
confidence: 84%
“…Although atherosclerosis plays the main role in the pathogenesis, inflammatory aortic aneurysms present a minor subgroup, with an incidence ranging from 2.2-18.1% of the total number of abdominal aortic aneurysms [2]. Although the standard treatment of all aortic aneurysms still remains open surgical repair, endovascular aneurysm repair has shown promising early and midterm results [3][4][5].…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Resolution of periaortic fibrotic tissue after surgery for IAAA is still debated. Some investigators have reported complete resolution whilst others have noted partial regression and even persistence of the inflammatory cuff [74][75][76]. New low-grade periaortic fibrosis has been reported after endovascular repair in a small number of patients [76].…”
Section: Treatmentmentioning
confidence: 99%
“…The material that has become favoured over the years is woven polyester (Dacron). steel is currently used for both self-expanding and balloon expandable varieties of stents, whereas Polyester and expanded polytetrafluoroethylene (ePTFE) form the basis of current stent-graft nitinol is only currently used for the self-expanding varieties [26].…”
Section: Delivery Systemsmentioning
confidence: 99%